2010
DOI: 10.5141/jefb.2010.33.3.187
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cardinal temperature variation on the germination of Haloxylon aphyllum L. seeds

Abstract: Seed germination is a biological process that is affected by a variety of genetic and environmental factors. The cardinal temperature and thermal time are required for germination. The principal objective of this study was to identify and characterize variations in the base, optimum, and maximum germination temperatures of Haloxylon aphyllum L. from two seed sources, in order to establish models for use in predicting seeding dates. Mature H. aphyllum seeds were germinated at temperatures between 5 and 35ºC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
4
9
0
1
Order By: Relevance
“…Taghvaei et al (2010) reported similar results about the germination rate responses of Haloxylon aphyllum Khaef et al (2010) reported that the optimal temperature for the germination of Calotropis procera was 25 o C, and pointed out that germination increased until 35 o C and then decreased.…”
Section: Zahedan Dune Desert Seed Sourcesupporting
confidence: 65%
See 4 more Smart Citations
“…Taghvaei et al (2010) reported similar results about the germination rate responses of Haloxylon aphyllum Khaef et al (2010) reported that the optimal temperature for the germination of Calotropis procera was 25 o C, and pointed out that germination increased until 35 o C and then decreased.…”
Section: Zahedan Dune Desert Seed Sourcesupporting
confidence: 65%
“…The base temperatures were 20 o C and 19 o C in the Zahedan and Fars desert regions, respectively (Table 3). The range in base temperatures between two seed lots of milkweed (Calotropis procera) was 0.62 o C and 1.76 o C, but was not statistically significant, although it may be biologically significant (Taghvaei et al, 2010). Cardinal temperatures for germination of the medicinal and ...…”
Section: Zahedan Dune Desert Seed Sourcementioning
confidence: 96%
See 3 more Smart Citations